2021
DOI: 10.3390/app11062464
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Phase-Field Model Validation for Dissolution of Minerals

Abstract: Modelling of a mineral dissolution front propagation is of interest in a wide range of scientific and engineering fields. The dissolution of minerals often involves complex physico-chemical processes at the solid–liquid interface (at nano-scale), which at the micro-to-meso-scale can be simplified to the problem of continuously moving boundaries. In this work, we studied the diffusion-controlled congruent dissolution of minerals from a meso-scale phase transition perspective. The dynamic evolution of the solid–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 104 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…Both S and L are physical parameters that can be determined experimentally 34 or computationally. 29,35 The surface energy S (ref. 35) depends on the direction of the Miller planes.…”
Section: Simulation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Both S and L are physical parameters that can be determined experimentally 34 or computationally. 29,35 The surface energy S (ref. 35) depends on the direction of the Miller planes.…”
Section: Simulation Parametersmentioning
confidence: 99%
“…22-24. It has to a much lesser extent been employed in relation to the precipitation and dissolution processes involved in crystallization that is controlled by a discontinuous solute concentration at the solid-liquid interface, [25][26][27][28] and PF modelling of the crystallization of real systems with direct quantitative comparison to experimental data is rare. [29][30][31] According to reaction diffusion theory ionic crystals develop a diffuse interface of several tens of micrometres in solution 32,33 and the PF model is in principle well suited to provide quantitative results on microscopic and macroscopic scales for such systems. The model is appealing because it can provide information about properties such as the crystal growth rate and the growth mode.…”
Section: Introductionmentioning
confidence: 99%
“…30%. Based on the relationship between the diffusion coefficient, the open porosity and the pore morphology [68,69], D sou is set to be 5 orders of magnitude smaller than in its solution. As this is a crack scale model, it operates both with ion diffusivity in pore (crack) solution and effective diffusivity through porous matrix.…”
Section: Experimental Validationmentioning
confidence: 99%
“…In the literature, references with different focuses on the dissolution process can be found. It ranges from intrinsic dissolution experiments of single crystal dissolution , to analytical equations for predicting dissolution process and numerical models. Nevertheless, the basis of these experiments, calculations, and models is the dissolution behavior of each single substance used for these formulations. However, previous work has shown that the dissolution behavior of drugs is not limited only by diffusion and convection.…”
Section: Introductionmentioning
confidence: 99%